(untitled) (Bangladesh Pharmaceutical Journal, 2025)
Maternal separation (MS) is a commonly used paradigm in rodents that has been widely established as a model to study the long-term effects of early-life stress on brain function and behavior, eventually resulting in heightened anxious- and depressive-like behavior. The present study aimed to assess whether supplementation with aged garlic extract (AGE) could reduce the symptoms of adverse effects in mice. We used a battery of behavior tests such as forced swim test (FST), tail suspension test (TST), elevated plus maze (EPM) and open field test (OFT) to evaluate anxiety- and depressive-like behaviors. Our data demonstrated that aged garlic extract treatment markedly (p<0.05) improved the depressive-like behaviors of maternally separated mice. In particular, AGE treatment induced a marked (p<0.05) decrease in the immobility time in forced swim test and tail suspension test, which is indicative of a reduction in depressive-like behavior. In addition, AGE-treated mice spent more time in the open arms in the elevated plus maze and in the central area in the open field test, indicating a decrease in anxiety-like behavior. These findings indicate that AGE may represent a potential target for treating early life stress’s damage to mental health. The beneficial effects of such exposure likely reflect the antiinflammatory and anti-oxidant effects of AGE, which could potentially guard against stress-induced neuroinflammation and oxidative harm within the brain. More studies are necessary to elucidate the detailed molecular mechanism of AGE’s therapeutic effects and evaluate its translational potential in subjects at high risk of stress-related psychiatric disorders. Bangladesh Pharmaceutical Journal 28(2): 214-227, 2025 (July)